Evaluación del efecto de un nosode sobre plantas de tomate (Solanum lycopersicum) bajo condiciones controladas - Moya Macías, Agner Josue (2021)
Nosodes are highly diluted biological compounds, from diseased organisms from which it is possible to retain the processes of infection of pathogens in plants, activating the defense system. This research was carried out with the objective of evaluating the effect of nosodes in tomato plants infected with Fusarium oxysporum f. sp. Lycopersici under controlled conditions. All in a completely random design. As factors, three application techniques (Foliar-Edaphic-Injection) and three centesimal dilutions (6C-12C-30C) were evaluated. For this, the nosode was prepared from a strain of the pathogen F. oxysporum, following standardized methodologies and as a starting point for obtaining the centesimal dilutions. Later, tomato plants were infected using the cut and wound technique. The plants were previously inoculated with the nosode, in the defined concentrations, in three different ways: edaphic, foliar and injection. To evaluate the treatments, the severity percentage of Fusarium oxysporum f. sp. Lycopersici. Additionally, the health status of the plant was evaluated using morphometric variables. Treatment with soil application and 6C dilution considerably reduced disease symptoms in tomato crops by 50%. Likewise, the health status of the plants treated with nosode improved, increasing the response in all morphometric variables such as height 130 cm, root length 30 cm, fresh weight of leaf and stem 180 gr, fresh weight of root 30 gr , dry weight of leaf and stem 27 gr, dry weight of root 8.20 gr. The nosode made from F. oxysporum optimized all the variables evaluated in tomato plants, particularly the severity percentage. These results indicate potential to reduce the use of pesticides in tomato, contributing to its organic production. Key words: Homeopathic, Fusarium oxysporum, nosode, Solanum lycopersicum